2015
DOI: 10.1088/1674-1056/24/6/068505
|View full text |Cite
|
Sign up to set email alerts
|

Phosphor-free white light-emitting diodes

Abstract: The multiple color-matching schemes that could improve the color rendering index for phosphor-free white LEDs are discussed. Then we review a few of the recent research directions for phosphor-free white LEDs, which include the development of monolithic GaN-based white LEDs and hybrid integrated GaN-based and AlGaInP-based white LEDs. These development paths will pave the way toward commercial application of phosphor-free white LEDs in the coming years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Yang et al [15] found that switching the ferroelectric state of the BFO layer did not change the photovoltaic response. Guo et al [16] suggested that the sign of photocurrent could be independent of the direction of polarization when the modulation of the energy band induced by oxygen vacancies is large enough to offset that induced by polarization, whereas the oxygen vacancies act as shunts and trapping center due to their positively charged and higher mobility. Therefore, clearly more detailed studies are necessary to elaborate on the role of ferroelectricity and oxygen vacancies in enabling the photovoltaic effect and the switchable phenomenon.…”
mentioning
confidence: 99%
“…Yang et al [15] found that switching the ferroelectric state of the BFO layer did not change the photovoltaic response. Guo et al [16] suggested that the sign of photocurrent could be independent of the direction of polarization when the modulation of the energy band induced by oxygen vacancies is large enough to offset that induced by polarization, whereas the oxygen vacancies act as shunts and trapping center due to their positively charged and higher mobility. Therefore, clearly more detailed studies are necessary to elaborate on the role of ferroelectricity and oxygen vacancies in enabling the photovoltaic effect and the switchable phenomenon.…”
mentioning
confidence: 99%
“…Nowadays, InGaN/GaN multiple-quantum-well (MQW)based light-emitting diodes (LEDs) are widely used in general lighting, displays, backlighting, and communications [1][2][3] due to the tenability of the emitted light from near-ultraviolet to visible and up to near-infrared spectral range by tuning the In composition in the InGaN well layers (WLs). [4] However, there remain many difficulties in achieving high-performance LEDs, which need to be overcome.…”
Section: Introductionmentioning
confidence: 99%
“…Much attention has been paid to white light-emitting diodes (WLEDs) for solid-state lighting applications due to their excellent brightness, low power consumption, long lifetime, and environmental friendliness. [1][2][3] Generally, white light emission results from the use of phosphor to transform part of emissions of blue LEDs to the yellow-green spectral range. The transformation is related to an energy loss termed Stokes' loss, which is on the order of 25% and thus restricts the highest attainable phosphor-converted WLED efficiency to much less than 100%; [4,5] however, in principle, one can avoid the loss through the use of phosphor-free monolithic WLEDs, which are integrated by blue, green, and even red long-wavelength InGaN-based LEDs, since the nitride system can cover the entire spectral region of the emitted light from near-ultraviolet to near-infrared by adjusting the composition of InGaN alloy.…”
Section: Introductionmentioning
confidence: 99%